Cloud Computing Security Threats and Responses - Saurabh Kansal, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Currently some of the most preferred models of technology delivery are cloud computing models of technology, which have dramatically transformed data management and storage but have also resulted in sophisticated risks. In this paper, we will analysis the development of cloud security threats, typical threats, and new threats in multi-cloud environments. Security enhancements are outlined, and the array of shortcomings of previous security solutions are presented, as well as prospects and challenges related to compliance. It is found that for combating these threats, there is need for implementational security measures, responsive technologies and standardized policies across the world. New ideas like zero-trust security and cryptographic forms are also stated to address the risks. This review’s implication, therefore, is that there should be partnerships in realizing safer and more robust clouds.
Keywords: Cloud Computing; Security Threats; Attack Vectors; Multi-Cloud Environments; Regulatory Compliance; Encryption; Zero-Trust Architecture